Successive Searching Behaviour During Information Retrieval (IR) Interaction: Development of a New Line of Research - Spink, Amanda; Bateman, Judy; Griesdorf, Howard (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The study of successive searching, or user's pattern of search sessions in digital environments over time related to the same or evolving information problem, is developing as a new line of investigation. A growing body of studies is beginning to investigate and characterize the successive searching process. This area of research draws together information retrieval (IR) research. . .